Zayd al-Nar’s revolt in Basra and the position of Imam al-Rida (u) regarding it in the year (199 AH / 815 AD) - Abdul Zahra Al-Diraoui , Lect . Dr. Hadi (Basra studies journal, 2026)
The Abbasid state witnessed numerous revolutions was led by various segments of society, aiming to change the poor reality of the Islamic nation which they experienced due to the oppression of rulers over the people. Among these revolutions was the Zayd al-Nar Revolution in Basra in 199 AH. This revolution was chosen over others not to explore the causes and events of this revolution, but rather to demonstrate Imam al-Rida’s (peace be upon him) position on this revolution, given that its leader was his brother Zayd, the son of Imam al-Kadhim (peace be upon him( .